PENGARUH PEMBERIAN BOKASHI DAN NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SEMANGKA (Citrullus vulgaris Schard) - Syah, Muhadan '; Yetti, Husna '; Yoseva, Sri ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
ABSTRACT This study aimed to determine the effect of Bokashi and NPK on the growth and yield of watermelons. This research was conducted in farmers' fields Jalan Palembang, Kulim on KM15, Pekanbaru. The study lasted three months starting in December 2015 until March 2016. The study was conducted experimentally using a randomized block design (RCBD) factorial consisting of two factors: Bokashi and NPK with three replications. The first factor was Bokashi (M) which consists of three levels is:M1(5 ton / ha), M2 (7 tonnes / ha) M3 (10 ton / ha) and the second factor is the NPK (S) consisting of 3 levels namely: S1 (350 kg / ha), S2 (700 kg / ha),S3 (1050 kg / ha). Parameters those measured were plant length, number of leaves, flowering age, harvesting age, and fresh weight of fruit per plant. The results showed that the interaction of Bokashi and NPK application significantly affected the length of the plant, number of leaves, and the weight of fruit per plant. Award Bokashi 7 tonnes /ha and 350 kg NPK / ha gives good results on the growth and yield of watermelons.   Keywords: watermelon, Bokashi fertilizers, NPK.